2012
DOI: 10.1071/mf12210
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, survival and temporary emigration of bottlenose dolphins (Tursiops sp.) off Useless Loop in the western gulf of Shark Bay, Western Australia

Abstract: Capture-recapture models were used to provide estimates of abundance, apparent survival and temporary emigration of Indo-Pacific bottlenose dolphins (Tursiops sp.) in a 226-km 2 study area off The best fitting capture-recapture model suggested a random temporary emigration pattern and, when coupled with relatively high temporary emigration rates (0.33 (s.e. 0.07) -0.66 (s.e. 0.05)) indicated that the study area did not cover the entire ranges of the photo-identified dolphins. Apparent survival rate is a produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 44 publications
2
101
1
Order By: Relevance
“…Dolphin counts did, however, vary among the different surveys, suggesting a substantial detection bias. Other cetacean studies have also observed detection probabilities <1 (Shrestha 1989, Smith et al 1994, Timilsina et al 2003, WWF-Nepal 2006, Paudel et al 2014 and it is appropriate and important to account for these biases when determining population estimates, particularly for rare and endangered species (Nicholson et al 2012). We suggest that future surveys in an N-mixture model framework might benefit from measuring additional detection covariates at the scale of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…Dolphin counts did, however, vary among the different surveys, suggesting a substantial detection bias. Other cetacean studies have also observed detection probabilities <1 (Shrestha 1989, Smith et al 1994, Timilsina et al 2003, WWF-Nepal 2006, Paudel et al 2014 and it is appropriate and important to account for these biases when determining population estimates, particularly for rare and endangered species (Nicholson et al 2012). We suggest that future surveys in an N-mixture model framework might benefit from measuring additional detection covariates at the scale of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…This might have positive effects on population density, as niche segregation allows for increased carrying capacities compared with ecologically homogeneous populations [51][52][53]. In this context, it is important to note that Shark Bay appears to support one of the highest densities of bottlenose dolphins worldwide, estimated to be 0.53-0.92 dolphins km 22 in parts of the study area in WSB [54].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study site is not likely to encompass the entire home ranges of some individuals [45] figure S3. In the first column, individuals of both strategies had the same fitness benefits.…”
Section: Discussionmentioning
confidence: 99%